Cover Image. Issue 1 (16th December 2018) - Fukudo, Shin; Miwa, Hiroto; Nakajima, Atsushi; Kinoshita, Yoshikazu; Kosako, Masanori; Hayashi, Kenta; Akiho, Hiraku; Kuroishi, Kentaro; Johnston, Jeffrey M; Currie, Mark; Ohkusa, Toshifumi
Abstract : The cover image is based on the Original Article High‐dose linaclotide is effective and safe in patients with chronic constipation: A phase III randomized, double‐blind, placebo‐controlled study with a long‐term open‐label extension study in Japan by Shin Fukudo et al., DOI:10.1111/nmo.13487 .